Procedures in Investigations of Weapons for Mass Destruction (Kriminalističke teme, 2006)
The global political climate has had influence lately on the development of old and new organizations that are dealing with acts even more violent than before, and this all in order to meet their goals. Terrorists have threatened and used even more violent and even more deadly tactics and methods. Therefore, on the basis of an increased availability of resources in terms of weapons, and a demonstration of the same, there is no doubt that terrorists would in the upcoming period use weapons that are able to kill hundreds, even thousands of innocent civilians. Therefore, law enforcement agencies have to take on numerous initiatives and strengthen their existing policies of fight in order to curb this threat, known as weapons of mass destruction.